Association of healthy eating index-2015 and overactive bladder: a cross-sectional study - Hao, Xuanyu; Liu, Gang; Li, Dongyang (Frontiers in Nutrition, 2024)
Objective The aim of this cross-sectional study was to investigate the association of HEI-2015 and overactive bladder (OAB) in a large population. Methods Data were retrieved from the National Health and Nutrition Examination Survey (NHANES) 2005–2020 datasets. Univariate and multivariate logistic regression were performed to evaluate the association between HEI-2015 and OAB. The restricted cubic spline (RCS) model was conducted to investigate the dose–response relationship. Results Totally, this study included 29,206 participants with 6,184 OAB patients among them. The higher continuous HEI-2015 value was independently associated with lower OAB incidence (OR: 0.87; 95%CI: 0.78, 0.98). Similarly, the highest quartile categorical HEI-2015 was significantly associated with a lower OAB odds (OR: 0.72; 95%CI: 0.52, 0.99) when compared with the lowest quartile. The RCS curve also showed a favorable non-linear dose–response relationship between HEI-2015 and OAB. Conclusion A higher HEI-2015 had a favorable association with OAB and there was a non-linear dose–response relationship between them. We suggest adherence to the United States diet recommendation as a potential behavioral prevention of OAB. Large-scale long term prospective cohort studies across various regions are needed to verify the findings of this paper.